Crime biters! It's a doggy dog world - Greenwald, Tommy (New York Scholastic, 2016)
Jimmy is sure that his dog Abby is special. After all, it was Abby who (with the help of Jimmy & friends) helped nab the criminal Barnaby Bratford and shut down Barnaby's babysitting service, a front for robbing the nice folks of Quietville. Jimmy's parents, on the other hand, are starting to feel like Abby is one destructive little dog (she chewed up Mom's entire shoe collection ) and they insist on enrolling Abby in obedience training. The only problem is that the longer Abby's in class, the more normal (read: boring) she becomes. Jimmy's superhero crime-fighting vampire dog is slowly becoming just like every other dog. She doesn't even sneak out at night anymore At the same time Jimmy's friends (the Crimebiters) are realizing that there's just not very much crime to fight in their tiny town. But when Jimmy joins the lacrosse team & mysterious things start happening on and off the field, the Crimebiters realize that Abby better get back to her crime-fighting ways...and fast
K
600
K